The Role of Productive Women in Alleviating Poverty Through Strengthening Islamic Social Finance: A Study of Micro Waqf Banks in Indonesia - Ssonko Muhammedi; Raden Ali Pangestu; Ilyas Helmi Bin Mohd Yusof; Umar Akem (Sekolah Tinggi Ekonomi dan Perbankan Islam Mr. Sjafruddin Prawiranegara, 2024)
The nature of women in development has a big role not only in the economic foundation of households, in the use of Islamic social financial institutions. Poverty motivates women to develop their potential through opportunity, excellence, and equality. Attention to Islamic social finance namely zakat, infaq, sadaqa and waqf in Indonesia is increasing as awareness improves. Limited access of productive women to social financial institutions makes it difficult to obtain business capital. The study investigates the contribution of women to poverty alleviation through Islamic social finance. This study uses qualitative methods with a field study approach. The research location is at the Micro Waqf Bank Lan Taburo Lebak Banten, Indonesia. Data collection using interviews, observations, and literature studies. Data analysis techniques use triangulation with collection, reduction, presentation, and conclusions. The results showed that the role of productive women micro waqf bank customers utilizes Islamic social finance, namely managing business financing, increasing household income, creating household economic prosperity, strengthening community empowerment, and increasing waqf literacy. The research implies that the greater the role of productive women utilizing Islamic social finance, the more positively it will contribute to poverty alleviation in Indonesia. This study was limited to women producing micro waqf banks who received benefits at one institution. Further research needs to be carried out in quantitative studies to find the dominant factor of alleviating harm using Islamic social finance.